PENGARUH KEPUASAN KERJA, KOMITMEN, DAN INTENSITAS TURNOVER TERHADAP PRESTASI KERJA KARYAWAN PADA PT. SUKA FAJAR LTD PEKANBARU - ', Rinaldi; ', Machasin; ', Sjahruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted at PT. suka fajar Ltd. located in Jalan Belimbing Pekanbaru. The purpose of this study was to determine the effect of job satisfaction, commitment and intensity turnover significant effect on employee performance in PT. suka fajar Ltd Pekanbaru and to know which is more influential factor against employee performance. The population in this study were all employees who work in the company of PT. suka fajar Ltd., while the sampling is done by using the formula Slovin, in order to obtain 55 employees to be sampled. Data analysis tool that is used is the F test, t test and the coefficient of determination (R2)Based on the results of research and discussion, it is known that job satisfaction, organizational commitment and turnover intensity significant effect on employee performance, either partially (t test) or simultaneously (F test). This is evident from the t test and F test significant at the alpha level of 5%. Thus the first hipotisis this study may be accepted at the 95% confidence level. Employee satisfaction has the most dominant influence on employee performance compared with the effect of variable intensity organizational commitment and turnover, it is seen from the regression coefficients of each variable. Therefore, the second hypothesis of this study is also acceptableKeywords: Job Performance, Job Satisfaction, Organizational Commitment, Turnover Intensity